Beneficial Effects of Green Tea EGCG on Skin Wound Healing: A Comprehensive Review - Xu, Fa-Wei; Lv, Ying-Li; Zhong, Yu-Fan; Xue, Ya-Nan; Wang, Yong; Zhang, Li-Yun; Hu, Xian; Tan, Wei-Qiang (Molecules (Basel, Switzerland), 2021)
Epigallocatechin gallate (EGCG) is associated with various health benefits. In this review, we searched current work about the effects of EGCG and its wound dressings on skin for wound healing. Hydrogels, nanoparticles, micro/nanofiber networks and microneedles are the major types of EGCG-containing wound dressings. The beneficial effects of EGCG and its wound dressings at different stages of skin wound healing (hemostasis, inflammation, proliferation and tissue remodeling) were summarized based on the underlying mechanisms of antioxidant, anti-inflammatory, antimicrobial, angiogenesis and antifibrotic properties. This review expatiates on the rationale of using EGCG to promote skin wound healing and prevent scar formation, which provides a future clinical application direction of EGCG.